Responses of enzymatic activities within soil aggregates to 9-year nitrogen and water addition in a semi-arid grassland. (February 2015) - Wang, Ruzhen; Dorodnikov, Maxim; Yang, Shan; Zhang, Yongyong; Filley, Timothy R.; Turco, Ronald F.; Zhang, Yuge; Xu, Zhuwen; Li, Hui; Jiang, Yong
Abstract: Soil microorganisms secrete enzymes used to metabolize carbon (C), nitrogen (N), and phosphorus (P) from the organic materials typically found in soil. Because of the connection with the active microbial biomass, soil enzyme activities can be used to investigate microbial nutrient cycling including the microbial response to environmental changes, transformation rates and to address the location of the most active biomass. In a 9-year field study on global change scenarios related to increasing N inputs (ambient to 15 g N m −2 yr −1 ) and precipitation (ambient to 180 mm yr −1 ), we tested the activities of soil β-glucosidase (BG), N-acetyl-glucosaminidase (NAG) and acid phosphomonoesterase (PME) for three soil aggregate classes: large macroaggregates (>2000 μm), small macroaggregates (250–2000 μm) and microaggregates (<250 μm). Results showed higher BG and PME activities in micro-vs. small macroaggregates whereas the highest NAG activity was found in the large macroaggregates. This distribution of enzyme activity suggests a higher contribution of fast-growing microorganisms in the micro-compared with the macroaggregates size fractions. The responses of BG and PME were different from NAG activity under N addition, as BG and PME decreased as much as 47.1% and 36.3%, respectively, while the NAG increased by as much as 80.8%, which could imply better adaption of fungi than bacteria to lower soil pH conditions developed under increased N. Significant increases in BG and PME activities by as much as 103.4 and 75.4%, respectively, were found under water addition. Lower ratio of BG:NAG and higher NAG:PME underlined enhanced microbial N limitation relative to both C and P, suggesting the repression of microbial activity and the accompanied decline in their ability to compete for N with plants and/or the accelerated proliferation of soil fungi under elevated N inputs. We conclude that changes in microbial activities under increased N input and greater water availability in arid- and semi-arid grassland ecosystems where NPP is co-limited by N and water may result in substantial redistribution of microbial activity in different-sized soil particles. This shift will influence the stability of SOM in the soil aggregates and the nutrient limitation of soil biota. Highlights: Microbial biomass distribution among soil fractions was different from soil enzymes. Nitrogen addition decreased microbial activity while water addition stimulated it. N addition reduced β-glucosidase (BG) but increased N-acetyl-glucosaminidase (NAG). A lower BG:NAG ratio underlined microbial N limitation relative to C.